1984
DOI: 10.1002/hep.1840040317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of βrenergic Blockade with Propranolol in Patients with Cirrhosis

Abstract: Fourteen patients with cirrhosis and bleeding esophageal varices were treated with propranolol. The dose of propranolol was determined by decreasing the resting heart rate by 25% 12 hr after an oral dose of propranolol which was given twice a day. Significant decreases in the hepatic venous pressure gradient and cardiac output after 1 month of propranolol administration was observed. To assess beta-adrenergic blockade, the isoproterenol test and plasma propranolol levels were evaluated. Increasing doses of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This was 53 titrated until a 20 to 25% reduction in resting heart rate (Bercoff et al 1984) occurred 6 hours after administration, or until the maximum permitted dose was reached (320mg of long-acting propranolol once daily) [Leahey et al 1980]. Patients were evaluated every 2 months and the end-points were death or haemorrhage.…”
Section: Study Protocolmentioning
confidence: 99%
“…This was 53 titrated until a 20 to 25% reduction in resting heart rate (Bercoff et al 1984) occurred 6 hours after administration, or until the maximum permitted dose was reached (320mg of long-acting propranolol once daily) [Leahey et al 1980]. Patients were evaluated every 2 months and the end-points were death or haemorrhage.…”
Section: Study Protocolmentioning
confidence: 99%
“…In patients with cirrhosis, nonselective beta-blockers (NSBB) prevent primary and secondary gastrointestinal haemorrhage and reduce the mortality rate associated with bleeding (1)(2)(3)(4). However, the beneficial effect of NSBB in advanced cirrhosis has recently been questioned giving rise to a heated debate (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The dose and the route of propranolol administration were different in patients with cirrhosis with and without surgical portacaval shunts, but the changes in heart rate and cardiac output in the three groups provide some assurance that the assessment of p-adrenergic blockade was comparable. 1 This finding demonstrated that hepatic arterial blood flow is modulated independently of the fall in cardiac output. The effect might be interpreted as an expression of hepatic arterial autoregulation to preserve liver perfusion, but a direct effect of propranolol on intrahepatic circulation cannot be excluded.…”
Section: Discussionmentioning
confidence: 86%